Comparison of a Standard and a High-Concentration Contrast Medium Protocol for MDCT Angiography of the Lower Limb Arteries - Meyer, B. C.; Klein, S.; Krix, M.; Aschoff, A. J.; Wacker, F. K.; Albrecht, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: To prospectively compare a compact bolus (CB) injection protocol using high-iodine concentration contrast medium with a standard bolus (SB) injection protocol at equi-iodine doses for run-off computed tomographic angiography (CTA). Materials and Methods: 64 patients with suspected peripheral arterial disease who underwent 40 or 64-slice run-off CTA were included in this IRB-approved study. Patients were randomized to undergo the CB protocol (32 patients, iomeprol 400mgI/mL, 100 mL, 4 mL/sec) or the SB protocol (32 patients, iomeprol 300mgI/mL, 134 mL, 4 mL/sec). Luminal contrast density (CD) values were measured and arterial opacification (AO) was scored (5-point scale). Cases of venous overlay or bolus overriding were documented. Results: Overall arterial CD was significantly higher with the compact bolus (CB: 279 ± 57HU, SB: 234 ± 32HU, p = 0.0017). Segmental CD was significantly higher (p< 0.05) in 7 of 16 evaluated segments. Patency-based comparison revealed superior AO in vessels with relevant (50 – 99 %) stenoses (CB: 4.54 vs. SB: 4.18, p = 0.04). Contrast bolus overriding without pathological reasons, i. e., acute occlusions, was noted in one patient in each group. Venous overlay was observed less frequently in the CB group (CB vs. SB: 12 vs. 19 patients, n. s.; 29 of 64 legs [45 %] vs. 44 of 64 legs [69 %], p = 0.01). Conclusion: At equi-iodine doses, the CB protocol led to a quantitatively and qualitatively higher arterial opacification compared to the SB protocol. Therefore, a CB protocol should be favored for run-off CTA.
Keywords: extremities; vascular; CT angiography